Cross-national public opinion about homosexuality: examining attitudes across the globe - Adamczyk, Amy (University of California Press, 2017)
The importance of religion, and the role of individual differences -- The importance of democracy and economic development -- Shaping attitudes in Protestant nations : a comparison of the United States, Uganda, and South Africa -- Understanding views in Muslim countries : an analysis of Malaysia, Indonesia, and Turkey -- The relatively liberal views of people from majority Catholic countries : an examination of Spain, Italy, and Brazil -- Investigating public opinion in Asian nations : Buddhism, Confucianism, and the importance of family ties in East Asia -- Shaping attitudes in Taiwan : a case study (Ok, but not in my family) -- Conclusion : other religions, outliers, and the future -- Appendix A. Countries included in WVS analysis by 2015 homosexuality laws and the nation's dominant religion -- Appendix B. WVS data and hierarchical models -- Appendix C. Additional macro-level indicators -- Appendix D. Details on content analysis of newspaper articles